Respuesta :
The sequence is A(n) = 6 [5 ^ (n-1) ]
Although, the formula may be applied to negative, zero and positive numbers, it does not make sense to talk about the -1 or zero term.
Ther first term is A(1), where n = 1, then the answer should be n =1.
Answer: n = 1
Here you can see that you the formula may be applied, but this does not mean that you can do it, because n = 1 is used to define the first term.
For n = -1, A(1) = 6 [5^-2] = 6/ 5^2
For n = 0, A(0) = 6[5^-1] = 6/5
For n = 1, A(1) = 6 [5^0] = 6
For n =2, A(2) = 6 [5^1] = 6*5
For n = 3, A(3) = 6[5^2] = 6*5^2
Although, the formula may be applied to negative, zero and positive numbers, it does not make sense to talk about the -1 or zero term.
Ther first term is A(1), where n = 1, then the answer should be n =1.
Answer: n = 1
Here you can see that you the formula may be applied, but this does not mean that you can do it, because n = 1 is used to define the first term.
For n = -1, A(1) = 6 [5^-2] = 6/ 5^2
For n = 0, A(0) = 6[5^-1] = 6/5
For n = 1, A(1) = 6 [5^0] = 6
For n =2, A(2) = 6 [5^1] = 6*5
For n = 3, A(3) = 6[5^2] = 6*5^2